Suitability of the Independent Curriculum Teaching Modules with National Education Standards - Reza Oliviranti; Susilawati; Sirniawati (Proceedings Series on Social Sciences & Humanities, 2024)
On February 11st, 2022, the Minister of Education in Indonesia has formulated a new curriculum, named the Merdeka Curriculum. Therefore, the development of learning modules based on the new curriculum standards is necessary. Additionally curriculum development must adapt to the current era, which is the era of digitalization. Whereas teachers must continue to follow changes following the current curriculum as a form of adjustment. This study aims to determine the extent of teachers' understanding of the suitability of teaching modules under the Merdeka Curriculum. This study thoroughly explores the suitability of teaching modules made by teachers under the Ministry of Education and Culture's Merdeka Curriculum teaching modules. This research approach model uses case studies to be examined thoroughly. The data in this study were obtained through interviews and content analysis checklists with one 8th grade English teacher at SMPN 1 TALUN. The findings show that the conformity between the teaching module made by the teacher and the teaching module under the Ministry of Education and Culture can be declared appropriate because many components have been fulfilled. There are only a few that are not attached.